(A)phantasia and severely deficient autobiographical memory: Scientific and personal perspectives. (August 2018) - Watkins, Nicholas W.
Abstract: I address two interlinked aspects of the diversity in our experiences of memory and the mind's eye. I summarise the long-appreciated role of imagery in mathematics and the physical sciences, and contrast it with the evidence that some scientists have had limited or zero imagery. I then recount the story of how I became aware of my own lack of mental imagery, and the accompanying deficit in my episodic memory, how I have sought scientific understanding of these conditions, and how they have affected my life.